Identification of the Recombinant Plasmodium vivax Surface-Related Antigen as a Possible Immune Evasion Factor Against Human Splenic Fibroblasts by Targeting ITGB1 - Fu, Haitian; Lu, Jiachen; Zhang, Xinxin; Wang, Bo; Sun, Yifan; Lei, Yao; Shen, Feihu; Kassegne, Kokouvi; Han, Eun-Taek; Cheng, Yang (Frontiers in Cell and Developmental Biology, 2021)
Plasmodium vivax-infected erythrocytes can enter the spleen and evade spleen clearance to establish chronic infections. However, the mechanism underlying P. vivax immune evasion in the spleen is still unclear. Human splenic fibroblasts (HSF), also known as barrier cells, play an essential role in immune function of spleen. A hypothesis holds that P. vivax-infected erythrocytes induce spleen structural remodeling to form barrier cells. Subsequently, these infected erythrocytes can selectively cytoadhere to these barrier cells to escape spleen clearance. In this work, P. vivax surface-related antigen (PvSRA), an exported protein on infected erythrocyte membrane, was found to be able to bind with HSF. Considering the above hypothesis, we speculated that PvSRA might be involved in P. vivax immune evasion by changing HSF cell performance. To investigate this speculation, RNA sequencing, protein microarray and bioinformatics analysis technologies were applied, and in vitro validations were further performed. The results showed that PvSRA attracted HSF migration and interacted with HSF by targeting ITGB1 along with changes in HSF cell performance, such as focal adhesion, extracellular matrix, actin cytoskeleton and cell cycle. This study indicated that PvSRA might indeed participate in the immune evasion of P. vivax in the spleen by changing HSF function through PvSRA-ITGB1 axis.